Pengaruh Financial Literacy, Lifestyle Hedonis Dan Sikap Keuangan Pribadi Terhadap Perilaku Keuangan Mahasiswa Di Kota Batam - Yanti, Indah Yuli; Tipa, Handra (Prosiding, 2024)
Managing financial behavior is very important for setting financial priorities and managing money well, but according to surveys, many students don't do it. Often, a person's failure in managing their finances is not caused by low income, but rather due to the individual's lack of knowledge in managing personal finances and excessive living habits. Therefore, financial behavior needs to be paid attention to in order to create a better individual financial situation. Several factors, including Financial Literacy, Hedonic Lifestyle, and personal financial attitudes, can cause this financial behavior problem. The aim of this research is to analyze the influence of financial literacy, hedonic lifestyle and personal financial attitudes on the financial behavior of students in Batam City, both partially and simultaneously. The data analysis methods used in this research are multiple linear regression, classical analysis, partial and simultaneous testing. This research is quantitative and uses the SPSS 27 program. Data is collected primary and distributed via Google Form. The research results show that Financial Literacy partially has a positive effect on the financial behavior of students in Batam City; Hedonic lifestyle does not have a positive effect on the financial behavior of students in Batam City; and personal financial attitudes and financial knowledge simultaneously have a positive effect on students' financial behavior in Batam City. The dependent variable is influenced by 84.5% by the independent research variable, and variables outside the research influence the remaining 15.5%.